LANGUAGE USE AND COMMUNICATION SKILLS FOR FLIGHT ATTENDANTS - Yudi Setyaningsih (Jurnal Bahasa Lingua Scientia, 2015)
Speaking and listening skills to flight attendants having international routes are very important to support their performance when dealing with passengers. The International Civil Aviation Organization (ICAO) in 1951 and 2004 issued an announcement that English became the compulsory language used for international aviation. Moreover, the Federal Aviation Administration (FAA), in 1994, required flight attendants to understand sufficient English to communicate, coordinate, and perform all related safety duties on board. This article suggests some methods in teaching English for pre-service flight attendants. As speaking and listening play very important roles in the workplace of flight attendants, role play and speaking practice in the classroom can be very useful for pre-service flight attendants when they are still in the training center. Role plays with topics related with the real work situation such as boarding, seating, announcement, meals and drink service, personal approach as well as farewell should be provided for pre-service flight attendants together with pronunciation practice. To increase the effectiveness of the English course, additional English materials with the help of technology such as videos on airlines safety demonstration, announcement, and other recordings related with the use of polite languages as well as in-flight vocabulary could be used to train the listening skill. The rapid development in technology can also be an advantage in equipping flight attendants with materials in cultural issues. Flight attendants need cultural sensitivity when dealing passengers with different cultural backgrounds; therefore, increasing their cross-cultural understanding is very important.